The Role of Bank Loans in Monetary Policy Transmission in Malaysia - Hsing, Yu (The Economics and Finance Letters, 2014)
This study examines whether the bank lending channel holds for Malaysia based on a simultaneous-equation model consisting of the demand for and supply of bank loans. The three-stage least squares method to employed to estimate regression parameters. There is evidence of the bank lending channel for Malaysia because bank loan supply reacts negatively to the interbank rate and because monetary easing to purchase government bonds leads to more bank deposits and bank loan supply. In addition, depreciation of the Malaysian ringgit or a higher world interest rate results in a decrease in bank loan supply.